Pengaruh Pelayanan dan Kepuasan dengan Dampaknya pada Loyalitas Pasien di Klinik Bakti Praja Medika Karawang - Trisnaryan Pratama, Fahri; Acep Rohendi; Dasrun Hidayat (Da'watuna: Journal of Communication and Islamic Broadcasting, 2024)
The purpose of this study is to find out and analyze: (1) Service Quality; (2) patient satisfaction; and (3) The Effect of Service Quality and Patient Satisfaction on Patient Loyalty at Bakti Praja Medika Karawang Clinic, both simultaneously and partially. The research method used in this study is Applied research is quantitative research with a cross sectional approach. The unit of analysis in this study was the parties related to the inpatients of Bakti Praja Medika Karawang Clinic with a sample of 120 people. Based on the results of the study, it was found that the quality of service of Bakti Praja Medika Karawang Clinic had a negative and insignificant effect on patient loyalty. For patient satisfaction, Bakti Praja Medika Karawang Clinic has a positive effect and more dominantly affects patient loyalty. Patient loyalty of Bakti Praja Medika Karawang Clinic can generally be said to be good. While simultaneously both variables are equally influential, and partially only patient satisfaction is more dominantly influential. Because Patient Satisfaction predominantly affects Patient Loyalty, it becomes a top priority in increasing Patient Loyalty. Therefore, Bakti Praja Medika Karawang Clinic is advised to consistently maintain patient satisfaction carried out to patients, so that they will become patients who have high loyalty. Word